Pendidikan Karakter Dalam Tradisi Keagamaan Masyarakat Muslim Papua Barat - Akramun Nisa (Al-Riwayah : Jurnal Kependidikan, 2020)
This research is an effort to understand the meaning of character education in the religious traditions of the Muslim community of West Papua. The techniques used in the data collection process are interviews, observation and documentation. The results obtained indicate that of the eight religious traditions analyzed, there are ten values of character education. Of the ten values of character education are dominated by religious values and values of appreciation, especially in the tradition of safar bathing, gendang sahur, commemoration of the night of lailatu qadr, the implementation of aqiqah and qurban, maulid derivatives and maulid fakalah, tombormark and the tradition of picking up khatibs. Character education learning based on local wisdom is actually an alternative consideration in teaching and instilling wisdom values in the minds, paradigms, and beliefs of students by emphasizing the heart and reason in shaping character